Wait Times for Gastroenterology Consultation in Canada: The Patients’ Perspective - WG Paterson (Canadian Journal of Gastroenterology, 2010)
Long wait times for health care have become a significant issue in Canada. As part of the Canadian Association of Gastroenterology’s Human Resource initiative, a questionnaire was developed to survey patients regarding wait times for initial gastroenterology consultation and its impact. A total of 916 patients in six cities from across Canada completed the questionnaire at the time of initial consultation. Self-reported wait times varied widely, with 26.8% of respondents reporting waiting less than two weeks, 52.4% less than one month, 77.1% less than three months, 12.5% reported waiting longer than six months and 3.6% longer than one year. One-third of patients believed their wait time was too long, with 9% rating their wait time as ‘far too long’; 96.4% believed that maximal wait time should be less than three months, 78.9% believed it should be less than one month and 40.3% believed it should be less than two weeks. Of those working or attending school, 22.6% reported missing at least one day of work or school because of their symptoms in the month before their appointment, and 9.0% reported missing five or more days in the preceding month. A total of 20.2% of respondents reported being very worried about having a serious disease (ie, scored 6 or higher on 7-point Likert scale), and 17.6% and 14.8%, respectively, reported that their symptoms caused major impairment of social functioning and with the activities of daily living. These data suggest that a significant proportion of Canadians with digestive problems are not satisfied with their wait time for gastroenterology consultation. Furthermore, while awaiting consultation, many patients experience an impaired quality of life because of their gastrointestinal symptoms.